RESEÑA de: Reviriego Picón, Fernando; De Vicente Martínez, Rosario. El cine carcelario. Valencia : Tirant lo Blanch, 2015 - Gudin Rodríguez-Magariños, Faustino (Revista de Derecho de la UNED (RDUNED), 2015)
-